(untitled) (Texas Journal of Philology, Culture and History, 2023)
Oil has been a major driver of political and economic change in the 20th century, and it has not only represented a phase of economic construction for oil-producing countries, but also resulted in several political and economic consequences worldwide. Iran’s economy, in particular, has been heavily reliant on oil imports since the discovery of its vast oil reserves at the end of the 19th century in southern Iran. The significance of Iran’s oil increased after World War II (1939-1945), as Iranian oil reserves became the only reserves for the allies in the East. During that era, Iran’s economy was completely subordinated to the Western economy, as Iran was considered an important source of energy and a large market for Western products. For Western countries, Iran’s separation from the market was equivalent to abandoning half of the Middle East’s wealth. Iran’s economic importance was due to its economic potential as the first country to discover oil in the region in 1908, the first to produce and export oil in 1912, and the first to confront global companies by nationalizing its oil industry in 1951. The Iran-Iraq War created critical economic conditions that forced Iran to reduce its consumption of goods and services, and the Iranian people redirected their efforts towards supporting the war and actively contributing to some of its costs. However, due to the continued war, this support decreased, and the Iranian government began supporting private consumption in an attempt to strengthen the domestic front and continue the war. This research is divided into an introduction and three sections. The first section discusses the economic developments in Iran before the Iranian Revolution and examines the economic conditions in Iran after World War II and after the 1979 revolution. The second section reviews the role of the bazaar in the Iran-Iraq War of 1980- 1988, while the third section examines the economic developments in Iran during this period (1980-1988), highlighting the most important features of these developments.